1992
DOI: 10.1042/cs0830615
|View full text |Cite
|
Sign up to set email alerts
|

Salbutamol, a β2-adrenoceptor agonist, increases skeletal muscle strength in young men

Abstract: 1. beta 2-Adrenoceptor agonists have been shown to increase rapidly lean body mass and reverse muscle wasting in several animal models of human illness. However, no published information is available for humans. In the present study, we investigated the effects of a slow-release preparation of salbutamol or a placebo on skeletal muscle functional capacity in 12 healthy men. The strength of different muscle groups was measured on two occasions before and after 14 and 21 days of treatment. 2. No significant chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
128
1
7

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(144 citation statements)
references
References 7 publications
8
128
1
7
Order By: Relevance
“…It has been previously reported that SMN is phosphorylated at serines 28 and (8,12,14). ␤-Adrenergic agonists have been shown to improve muscle strength in human subjects with healthy and diseased muscle (29)(30)(31), and daily albuterol treatment had beneficial effects in an open-label pilot study in SMA type II and III patients (16). Salbutamol has been also been shown to increase SMN protein levels in patient-derived fibroblasts (1).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that SMN is phosphorylated at serines 28 and (8,12,14). ␤-Adrenergic agonists have been shown to improve muscle strength in human subjects with healthy and diseased muscle (29)(30)(31), and daily albuterol treatment had beneficial effects in an open-label pilot study in SMA type II and III patients (16). Salbutamol has been also been shown to increase SMN protein levels in patient-derived fibroblasts (1).…”
Section: Discussionmentioning
confidence: 99%
“…Although the potential therapeutic role for clenbuterol in muscular dystrophy has received much attention (Maltin et al 1987(Maltin et al , 1993Martineau et al 1992;Zeman et al 1994;Hayes & Williams 1994;Dupont-Versteegden et al 1995), the majority of these studies have investigated only whether clenbuterol alters the mass and isometric force-producing capacity of isolated muscles. Whether clenbuterol affects the dynamic properties of dystrophic skeletal muscle has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic treatment with clenbuterol, a âµ-adrenoceptor agonist, has been proposed as a treatment to reverse the muscle atrophy observed with ageing (Carter et al 1991), denervation (Maltin et al 1987(Maltin et al , 1993Zeman et al 1987;Agbenyega & Wareham, 1990), muscle unloading (Delday & Maltin, 1997) and muscle wasting diseases, such as muscular dystrophy (Maltin et al 1987(Maltin et al , 1993Martineau et al 1992;Zeman et al 1994;Dupont-Versteegden, 1996). It is well established that clenbuterol treatment increases muscle mass in a number of different species (Kim & Sainz, 1992) with an increased protein synthesis andÏor decreased protein degradation proposed as the mechanism for the hypertrophy of skeletal muscle (Choo et al 1992;Moore et al 1994).…”
mentioning
confidence: 99%
“…Also in humans beta2 agonists, when administered orally, intravenously or intramuscularly, may increase skeletal muscle mass or their force depending on the dose and on the duration of treatment [34][35]. Ventilatory endurance and Pi max were also increased after salbutamol treatment [35].…”
Section: Beta-2-adrenergic Drugsmentioning
confidence: 99%
“…Ventilatory endurance and Pi max were also increased after salbutamol treatment [35]. On the contrary some experiments failed in demonstrating that inhalation of salbutamol or salmeterol can improve the performances of healthy or asthmatic athletes [36-37-38] at therapeutic doses.…”
Section: Beta-2-adrenergic Drugsmentioning
confidence: 99%